Metropolitan air pollution abatement and industrial growth: Global urban panel analysis of PM10, PM2.5, NO2 and SO2. Issue 1 (2nd January 2022) - Leffel, Benjamin; Tavasoli, Nikki; Liddle, Brantley; Henderson, Kent; Kiernan, Sabrina
ABSTRACT: This study re-scales analysis of global environmental change down to the city-level, where it is becoming increasingly significant, to examine the relationship between air pollution abatement and industrial growth. Treadmill of Production theorists argue that economic growth leads to increased pollution, while Environmental Kuznets Curve research suggests that income increases initially lead to pollution increases, but begins to result in reductions after an economy transitions from manufacturing to services-based industries. We investigate whether growth in specific services industries is associated with pollution abatement in the presence of increasing income. For 96 of the world's largest metropolitan areas, we test the effects of panel data on income, growth across several services industry sectors and other controls on levels of course particulate matter (PM10 ), fine particulate matter (PM2.5 ), Nitrogen Dioxide (NO2 ) and Sulfur dioxide (SO2 ) during 2005–2017. We find that reductions of all four air pollutants are associated with local growth in public administration, environmental and health services industry sectors linked specifically to government spending, while pollution increases are associated with growth in manufacturing and mining industries. This affords important nuance to the debate on the reconcilability of economic growth and environmental protection, and on a more spatially granular scale.